Excretion/secretion products from Schistosoma mansoni adults, eggs and schistosomula have unique peptidase specificity profiles - Dvořák, Jan; Fajtová, Pavla; Ulrychová, Lenka; Leontovyč, Adrian; Rojo-Arreola, Liliana; Suzuki, Brian M; Horn, Martin; Mareš, Michael; Craik, Charles S; Caffrey, Conor R; O'Donoghue, Anthony J (Biochimie, 2016)
Schistosomiasis is one of a number of chronic helminth diseases of poverty that severely impact personal and societal well-being and productivity. Peptidases (proteases) are vital to successful parasitism, and can modulate host physiology and immunology. Interference of peptidase action by specific drugs or vaccines can be therapeutically beneficial. To date, research on peptidases in the schistosome parasite has focused on either the functional characterization of individual peptidases or their annotation as part of global genome or transcriptome studies. We were interested in functionally characterizing the complexity of peptidase activity operating at the host-parasite interface, therefore the excretory-secretory products of key developmental stages of Schistosoma mansoni that parasitize the human were examined. Using class specific peptidase inhibitors in combination with a multiplex substrate profiling assay, a number of unique activities derived from endo- and exo-peptidases were revealed in the excretory-secretory products of schistosomula (larval migratory worms), adults and eggs. The data highlight the complexity of the functional degradome for each developmental stage of this parasite and facilitate further enquiry to establish peptidase identity, physiological and immunological function, and utility as drug or vaccine candidates.
Keywords: Animals; schistosomiasis mansoni; Schistosomiasis mansoni; proteolýza; Proteolysis; Helminth Proteins; vazebná místa; Substrate Specificity; sekvence aminokyselin; lidé; Molecular Sequence Data; Amino Acid Sequence; ovum; stadia vývoje; proteasy; Peptide Hydrolases; molekulární sekvence - údaje; interakce hostitele a patogenu; proteiny červů; Ovum; Life Cycle Stages; zvířata; Host-Pathogen Interactions; substrátová specifita; Schistosoma mansoni; Binding Sites; Humans